O uso de realidade virtual em programas de reabilitação cardiovascular - Costa, Ariele dos Santos (2021)
Introduction: Cardiovascular rehabilitation (CVR) is defined as a necessary activity to ensure best physical, psychological and social conditions, for people with cardiovascular disease (CD), being considered an important low - cost non - pharmacological treatment. New tec hnologies in health field, especially in CVR programs, using virtual reality (VR), are shown as promising assistants with the objective of increasing adherence and satisfaction to programs. Objective: Map available evidence to provide an overview of the us e of VR in the context of CVR. Methods: This is a study based on scope review, that were researched studies using VR, interfaces like glasses in CVR programs with clinical and / or surgical patients. The databases used were: Pubmed, Medline, Lilacs, PEDro, Science Direct, Cochrane Database of Systematic Reviews e JBI Database of Systematic Reviews and Implementation Reports Journal. Results: RV in CVR programs has been described as safe and viable and has resulted in improve cardiorespiratory capacity, in a ddition to being motivating. Conclusion: VR can be considered a complementary tool in CVR programs, allowing to improve performance and adherence to programs.